Association of polyunsaturated fatty acids with improved heart rate variability and cardiovascular events in patients with end-stage renal disease receiving maintenance dialysis: a systematic review and meta-analysis of randomized controlled trials. Issue 17 (21st July 2021) - Chou, Chu-Lin; Chen, Jin-Shuen; Kang, Yi-No; Chen, Yuan-Jen; Fang, Te-Chao
Abstract : Objective : Apart from dietary restriction and medical therapy, the benefits of cardiovascular protection offered by polyunsaturated fatty acid (PUFA) supplements in patients with ESRD receiving maintenance dialysis remain unclear. Abstract : Objective : Apart from dietary restriction and medical therapy, the benefits of cardiovascular protection offered by polyunsaturated fatty acid (PUFA) supplements in patients with ESRD receiving maintenance dialysis remain unclear. This systematic review and meta-analysis examined the effects of PUFAs on blood pressure, heart rate (HR), HR variability (HRV), and cardiovascular disease (CVD) prognosis. Methods : We identified randomized controlled trials (RCTs) from Embase, PubMed (including MEDLINE), and Web of Science. We included seven RCTs that involved 724 patients with ESRD receiving dialysis and PUFA supplements. Results : The data indicated that compared with the control group, the PUFA group demonstrated decreased cardiovascular events (Peto odds ratio = 0.52, 95% confidence interval [CI] = 0.32 to 0.85, P = 0.009) and HRV (changes in the mean HR [mean difference = −2.59, 95% CI = −4.91 to −0.26, P = 0.03, I 2 = 0%]; mean RR interval [MD = 29.03, 95% CI = 5.43 to 52.63, P = 0.02, I 2 = 0%]; mean of the standard deviation of all normal RR intervals for all 5 min segments [MD = 2.73, 95% CI = 0.48 to 4.99, P = 0.02, I 2 = 0%], and square root of the mean of the sum of the squares of differences between adjacent intervals [MD = 2.03, 95% CI = 0.04 to 4.03, P = 0.05, I 2 = 0%]). Conclusion : PUFA supplements appeared to improve CVD prognosis in patients receiving dialysis. Additional RCTs with longer follow-up periods need to clarify the benefits of PUFA supplements in this patient population.